DIGITIZATION OF LAND RESOURCES MANAGEMENT: WORLD EXPERIENCE AND DOMESTIC REALITIES (INNOVATIVE ECONOMY, 2023)
Putsenteilo P.R., Kostetskyi Ya.I., Bryk M.M. DIGITIZATION OF LAND RESOURCES MANAGEMENT: WORLD EXPERIENCE AND DOMESTIC REALITIESPurpose. The aim of the article is a diagnostics of the global experience of land management and determination of the possibility of its implementation in Ukrainian practice in the context of digitalization.Methodology of research. The theoretical and methodological basis of the study is the scientific works of scientists on land relations in the agricultural sector of foreign countries. General scientific and special methods were used to achieve the set goal: the dialectical method of scientific knowledge – to consider the essence of land relations; synthesis – to clarify the relationships between subjects of land relations; graphic – for visual display of the obtained results; abstract and logical method – for forming research conclusions and proposals.Findings. The meaning and role of land relations is revealed, various approaches to determining their economic essence are considered. An analysis of current land relations in different countries of the world was carried out; international experience of land policy mechanisms was highlighted. The main directions of the world experience in regulating the agricultural land market are highlighted. The theoretical background of the main postulates of digitalization of land resources management is outlined.Originality. Modern approaches of scientists to the interpretation of the concept of “land relations” are systematized and summarized. Under land relations, it is proposed to understand social relations between the state, economic entities and society, which arise in the process of ownership, use, as well as protection and reproduction of land. On the basis of the international experience of land relations, the priority areas of regulation of land relations in the context of digitalization are proposed.Practical value. The obtained results of the research can be used to improve land relations and increase the effectiveness of the functioning of the domestic agricultural sector in the conditions of digitalization. The introduction of digital technology tools will enable agricultural producers to collect large amounts of data, control the state of land resources and the rationality of their use at different levels of management.Key words: digitalization, smart land use, smart land management, land resources, land relations, cadastre, land policy, land market, rent.
Keywords: digitalization; smart land use; smart land management; land resources; land relations; cadastre; land policy; land market; rent.